Spatial and Temporal Dynamics of Hillslope‐Scale Soil Moisture Patterns: Characteristic States and Transition Mechanisms. Issue 4 (27th March 2015) - Martini, Edoardo; Wollschläger, Ute; Kögler, Simon; Behrens, Thorsten; Dietrich, Peter; Reinstorf, Frido; Schmidt, Karsten; Weiler, Markus; Werban, Ulrike; Zacharias, Steffen
Abstract : Recent advances in wireless sensor technology allow monitoring of soil moisture dynamics with high temporal resolution at varying spatial scales. The objectives of this study were to: (i) develop an efficient strategy for monitoring soil moisture dynamics at the hillslope scale using a wireless sensor network; and (ii) characterize spatial patterns of soil moisture and infer hydrological processes controlling the dynamics of such patterns, using a method of analysis that allows the identification of the relevant hydrological dynamics within large data sets. We combined soil hydrological and pedological expertise with geophysical measurements and methods from digital soil mapping for designing the monitoring setup for a grassland hillslope in the Schäfertal catchment, central Germany. Hypothesizing a wet and a dry soil moisture state to be characteristic of the spatial pattern of soil moisture, we described the spatial and temporal evolution of such patterns using a method of analysis based on the Spearman rank correlation coefficient. We described the persistence and switching mechanisms of the two characteristic states, inferring the local properties that control the observed spatial patterns and the hydrological processes driving the transitions. The spatial organization of soil moisture appears to be controlled by different processes in different soil horizons, and the topsoil's moisture does not mirror processes that take place within the soil profile. The results will help to improve conceptual understanding for hydrological model studies at similar or smaller scales and to transfer observation concepts and process understanding to larger or less instrumented areas.